Расчет турбинной ступени по зазорам как решение обратных аэродинамических задач в свободных кольцевых каналах - Субботович, Валерий Петрович; Юдин, Александр Юрьевич; Темченко, Сергей Александрович (НТУ "ХПИ", 2014)
Представлены результаты сравнения расчетов ступени осевой турбины с данными ее экспериментальных исследований. Расчеты выполнены с помощью нового метода расчета осесимметричного течения в свободных кольцевых каналах. Кольцевой канал рассматривается как чередующиеся участки двух типов: свободные участки и участки, загроможденные некоторыми устройствами, способными изменять углы закрутки потока. Получено хорошее совпадение расчетных и экспериментальных значений параметров потока.

The results of the comparison of computational and experimental data for the axial turbine stage have been given. The computations were done using a new method of the computation of axially symmetric flow in free circular channels. The method was specifically designed for the solution of optimal design problems for turbopmachine flow passes and it takes into consideration the peculiarities of optimization schemes and allows for a considerable paralleling of computational processes. The circular channel is presented as the alternate sections of two types: free sections and the sections blocked up by some devices that are able to change flow swirl angles. The working medium is compressible and nonviscous and the flow is steady, adiabatic, axially symmetric and without separation. The computations done allowed us to find the flow rate distribution, statistical pressure, axial and circumferential velocity components for the cascade height. A good coincidence of the calculated and experimental values of flow parameters has been obtained.
Turbine stage clearance design to solve reverse aerodynamic problems in free circular channels
Keywords: проточная часть; межвенцовый зазор; обратная задача; линия тока; flow pass; interrow clearance; inverse problem; current line; turbine stage